Potential and Prospect of Sweet Potatoes as a Basic Ingredient for Various Balinese Culinary in Badung Regency - I Ketut Suda; Prawita, Ni Ketut Riska Dewi; Wiartha, Nyoman Gede Mas; Sudiarta, I Nyoman; Jayendra, Putu Sabda (Jurnal Ilmiah Hospitality Management, 2025)
This study explores the potential and prospects of processing sweet potato as a basic ingredient for Balinese culinary in Abiansemal Dauh Yeh Cani Village, Abiansemal District, Badung Regency. The findings show that although sweet potato has great potential for making traditional Balinese snacks, such as chips and lempog, the main challenges are the difficulty raw materials on sustainable basis and the lack of interest among the younger generation to be involved in agriculture. Additionally, sweet potato-based dishes are less popular due to people’s habit of switching to modern food product. However, with the right approach, including education on processing, attractive packaging, and modern marketing strategies, sweet potato-based culinary products have potential prospects for development as popular Balinese souvenirs for both local markets and tourists.